2004
DOI: 10.1111/j.1523-1755.2004.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for renal replacement therapy in the Early Treatment Diabetic Retinopathy Study (ETDRS), Early Treatment Diabetic Retinopathy Study Report No. 26

Abstract: In this study, major modifiable risk factors such as hypertension, dyslipidemia, and hyperglycemia were found to be predictive of RRT. Other predictors were markers of vascular pathology and inflammation, proteinuria, hypoalbuminemia, and increased serum creatinine. Controlled clinical trials with treatment strategies that improve serum lipid levels, systemic blood pressure, glycemic control, and markers of inflammation may be important in furthering our knowledge on the pathogenesis of diabetic complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 36 publications
6
42
1
Order By: Relevance
“…The prevalence rates of foot ulcer and amputation were similar to what has been reported in other studies in the field [37][38][39][40][41]. Studies of both type 1 and type 2 diabetic patients also found that the presence of any retinopathy was associated with a higher risk of the development of ESRD [42,43]. Our study confirmed the high prevalence of diabetic and cardiovascular complications in diabetic dialysis patient.…”
Section: Diabetic Complications and Cardiovascular Diseasessupporting
confidence: 90%
“…The prevalence rates of foot ulcer and amputation were similar to what has been reported in other studies in the field [37][38][39][40][41]. Studies of both type 1 and type 2 diabetic patients also found that the presence of any retinopathy was associated with a higher risk of the development of ESRD [42,43]. Our study confirmed the high prevalence of diabetic and cardiovascular complications in diabetic dialysis patient.…”
Section: Diabetic Complications and Cardiovascular Diseasessupporting
confidence: 90%
“…Observational data suggest that dyslipidemia may increase albumin excretion and the rate of progression of diabetic nephropathy (105). Elevation of plasma cholesterol in both type 1 and 2 diabetic subjects and plasma triglycerides in type 2 diabetic subjects were predictors of the need for renal replacement therapy (106). Whereas these observations do not confirm that MNT will affect diabetic nephropathy, MNT designed to reduce the risk for CVD may have favorable effects on microvascular complications of diabetes.…”
contrasting
confidence: 45%
“…Our results are consistent with previous studies that hypertension, DM, hypertension, hyperlipidemia and CAD are independent risk factors for ESRD [16][17][18]. Besides of these findings, we also demonstrated a synergistic interaction between H. pylori infection and the risk factors for ESRD.…”
Section: Discussionsupporting
confidence: 82%